Boats and tents at the mouth of the Snake River, Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Mouth of Snake River, Nome, Alaska" Original image in Hegg Album 18, page 8. Original photograph by Eric A. Hegg 1221; copied by Webster and Stevens 318.A